Manajemen dan Pemantauan Energi Motor BLDC pada Mobil Listrik Berbasis IoT - Aditya Ilham Pradana; Eka Prasetyono; Ony Asrarul Qudsi; Era Purwanto; Sutedjo Sutedjo; Syechu Dwitya Nugroho; Lucky Pradigta S.R.; Diah Septi Y. (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
This paper presents a system design as a management and monitoring of energy consumption in BLDC motors that are applied to electric vehicle. Energy consumption settings are applied using the Pulse Amplitude Modulation principle by adjusting the input voltage on a BLDC motor. This setting uses a DC-DC converter with Buck Converter topology. This converter is designed with a maximum current capability of 20 A and an output voltage that varies from a range of 24 V - 56 V. To ensure the output voltage is always on the set point, the duty cycle of Buck Converter is set using proportional controls. The regulated energy consumption is monitored with modern technology, namely by using low energy components and with the IoT Devices principle. Based on the results obtained, this method can reduce energy consumption up to 36%, as well as monitoring stable energy consumption at reading sensor.